Combating corporate tax avoidance by requiring large companies to file their tax returns - Sikka Prem (Journal of Capital Markets Studies (JCMS), 2018)
Purpose - The purpose of this paper is to develop arguments for a public policy of requiring all large companies to make their tax returns publicly available. It is argued that such a policy would help to check tax avoidance, strengthen public accountability and secure fair competition. Design/methodology/approach - The policy proposal rests on notions of transparency and public accountability. Findings - The paper argues that the proposed policy is feasible. Research limitations/implications - The paper hopes to stimulate debates about the value of public filing of corporate returns and limits of public accountability. Social implications - The paper extends the range of public policies which might be able to check organised tax avoidance. Originality/value - It is one of the few papers to call for public filings of large company tax returns.
Keywords: R31; R32; C58; 330; Public accountability; Transparency; Tax avoidance; Large companies; Tax returns